Relevancia de la formación en identidad de género para los estudiantes de psicología de la Universidad Antonio Nariño sede Bogotá- presencial. (2023)
Gender identity has gone through multiple approaches. In relation to the practice of psychology, there is a need to understand what is the concept that psychology students have about the relevance in the formation of gender identity, in a career which has constant interaction with people